MARKETING PLANNING AS KEY FACTOR OF ENTERPRISE STRUCTURE COMPETITIVENESS - E. V. Omelchenko; O. B. Repkina (Модернизация, инновация, развитие, 2016)
Market planning in businesses dealing both with goods and services plays an important coordinating role, since it helps an enterprise to attain its inner consent, to determine development directions, to stimulate inner cooperation, to coordinate distribution of its resources and to formulate ways to solve tasks on the basis of which the company intends to reach its marketing aims. Specified in the article are market planning stages to be followed by a company engaged in the sphere of design services, compliance with the stages making it easier to develop the final marketing plan, to create new advantages both to stand competition at the chosen market and even to take leading positions there.